Behavioral responses vary with prey species in the social spider, Stegodyphus sarasinorum. (22nd April 2019) - Parthasarathy, Bharat; Somanathan, Hema
Abstract: Predators living in social groups often show consistent interindividual differences in prey capture behavior that may be linked to personality. Though personality predisposes individuals for certain behaviors, responses can also be influenced by context. Studies examining personality-dependent participation in prey capture have largely employed only one prey species, offering the predator no choice. In nature, predators encounter a range of prey species, therefore participation in or leading a prey capture event must also depend on prey attributes (e.g., size and risk). In the social spider Stegodyphus sarasinorum, collective prey capture is mediated by personality types as a consequence of which some individuals are consistently more likely to attack. Here, we examined if an individual's consistency to attack persisted within and between the 2 prey species (honeybees and grasshoppers) and if the same individuals attacked first with both prey species. Our results showed that interindividual differences in attacking persisted within and between the 2 prey species. Spiders showed greater participation in attacking grasshoppers relative to bees. Identities of the first attackers were not the same for bees and grasshoppers. Spiders showed greater consistency over time in attacking bees relative to grasshoppers. Bees attracted fewer attackers than size-matched grasshoppers. These results suggest that greater task specialization may be necessary to successfully subdue bees. Spiders handled bees more cautiously, which is likely to explain the observed plasticity in attacking the 2 prey species. Thus, participation in prey capture in social spiders is influenced by the attributes of prey species. Abstract : Social spiders collectively capture prey for their large colonies. However, some spiders are more likely to participate by leading attacks or by following attackers while others rarely participate in prey capture. Such differences between individuals are known to be due to individual personalities in social spiders. Here, we show that spiders in a colony show consistency to capture prey, but more importantly and for the first time, we show that participation in capturing prey depends on the prey species itself. The identities of spiders that attacked first were not the same when we used honeybees and grasshoppers as prey. Over time we found that spiders were less consistent in attacking grasshoppers relative to bees. Thus, our results suggest that spiders can modulate their behavioral responses in relation to prey species.